Microbiological and serological study of non-gonococcal urethritis with special reference to Mycoplasma genitalium. - Taylor-Robinson, D (1985)
Twenty-two men with non-gonococcal urethritis (NGU), 19 with gonorrhoea, and 22 without urethritis were examined for various micro-organisms. Chlamydia trachomatis was isolated from the urethra of 45% of men with NGU, 21% of those with gonorrhoea, but from none without urethritis. Ureaplasma urealyticum but not Mycoplasma hominis was recovered from a larger proportion of men with NGU than from those in the other groups. M genitalium was isolated presumptively from 32% of men with NGU, 12% of those with gonorrhoea, from 10% of men without urethritis, and from 42% of the men with NGU from whom chlamydiae were not isolated. U urealyticum, M hominis, and M genitalium were sought also in the rectum of men in the three groups. The first two micro-organisms were confined almost exclusively to homosexual men, whereas M genitalium was apparently not restricted in this way and was found particularly in this site in men with NGU. The latter mycoplasma may be a resident primarily of the intestinal tract. A fourfold or greater rise in the titre of antibody to C trachomatis was detected in about 20% of the patients with NGU, but not in other men. A similar rise in the titre of antibody to M genitalium was seen in 29% of the patients with NGU and in 12% of those without urethritis. A concomitant antibody response to M pneumoniae, which is antigenically related to M genitalium, was seen in one patient only. The responses to M genitalium suggest infection by this mycoplasma and indicate the need for further serological studies.